Post- Treatment Dilemma In Garment Selection For Breast Cancer Patients Fit Attribute: Reality or Fantasy - Norazean Miswat, (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
In contrast to disability people, academic research has neglected breast cancer patient needs for fit in garment selection. It is argued that this type of consumer deserve particular research attention. Most of the breast cancer patient facing a number of change after treatment, this includes physical change, psychology concern, and social concern. These changes lead to stigma or negative perception. This paper presents the results of exploratory research designed to explore in depth the fit preference in garment among breast cancer patients. Spontaneous speech of a ten informants was audio/visual-recorded and sketches as an artefact probe during the interview. Data were analyzed using inductive thematic analysis, and three key themes were found: loose cutting, actual size, and flexible. It was concluded that these breast cancer women’s had a hate-love relationship with clothes fit and sizing especially with ready-made clothing and used well-fitting clothes to upturn self-confidence, camouflage the flaws, and try to be normal as they can. Ideas for future instructions for research in these areas are deliberated.